Ecological study of fungi in pond ecosystem - Tiwari, K.L., *Deo Sajal Saju and (International Multidisciplinary Research Journal, 2011)
The distribution of fungal species in the pond water is determined by the various types of environmental factors. During present study Petriplate method containing potato dextrose agar (PDA) media had been adopted for survey of pond water fungi from one year March 2007 to February 2008. Total 91 fungal species (362 colonies) belonging to 45 fungal genera were isolated from Dumaratarai pond. During the present study Aspergillus terreus shows maximum percentage frequency (58.3%) which was followed by A. niger and A. sydowi with 50% frequency. Similarly maximum percentage contribution (87.01%) was encountered for group Anamorphic fungi, which were followed by group Zygomycotina (3.05%), Ascomycotina (8.01%) and minimum percentage contribution (1.94%) was encountered for group Mycelia sterilia. Aspergillus sp. was the leading genus with 28.73% contribution. Cladosporium sp. came behind and was represented by 15.46% contribution of gross total count, which was followed by Penicillium sp. with 8.29%, and Fusarium sp. with 5.24% contribution. The broadest spectrum of species were produced by Aspergillus (17species), Penicillium (11 species) Fusarium (04 species), Phoma (05 species) and Cladosporium (03).